Pianism of Volodymyr Horovits: the relationship of concertness and chamberity of the performing style - Ovcharenko-Pieshkova, Olena (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study. The topicality of the topic of the proposed exploration lies in the study of the specifics of the ratio of chamber and concert performance style on the example of the work of Volodymyr Horovyts. A complex methodology was applied, including biographical, comparative, and executive analysis methods. It has been investigated that the “genealogical” tree of V. Horovyts reaches the roots of the Viennese classical school, as well as representatives of the Romantic era. It has been found that the parameters of the chamber performance style prevail when the pianist interprets works close to a miniature; instead, concert performance is represented in works of various genres. However, it is substantiated that in the style of V. Horovyts, the mobile ratio of the two specified executive coordinates prevails. The conducted research opens up prospects for further understanding of the specifics of the relationship between the phenomena of concert and chamber performance style. The purpose of the article to reveal the specifics of the performance style of V. Horovyts from the point of view of the ratio of chamber and concert performance. The methodological basis of the research consists of the following methods: biographical (to understand the key stages of V. Horovyts life); performance analysis (in order to understand the specifics of V. Horovyts performance); comparative (when studying the specifics of the phenomena of chamber music and concert performance). Results and conclusions. Summarizing the results of the research, we note that V. Horovyts is definitely a performer of limitless artistic and technical possibilities and artistic will. A comprehensive study made it possible to reveal the specificity of the phenomena of chamber performance and concert performance. As the research showed, over time, the division of these categories became more and more conditional, as performers interpret musical works from the standpoint of individual performance style. Thus, the same work can change its performance and stylistic parameters. Based on the intonation-semantic resources of the work and the mentioned lifecreating circumstances, V. Horovyts synthesizes both types of performance style — chamber and concert, and his sensitive artistic ear allows him to move from one stylistic coordinate to another.